Root Canal Disinfection Articles with the Highest Relative Citation Ratios. A Bibliometric Analysis from 1990 to 2019 - Pilar Valderrama; Pilar Baca; Carmen Solana; Carmen María Ferrer-Luque (MDPI AG, 2021)
The relative citation rate (RCR) is a normalized article-level metric useful to assess the impact of research articles. The objective of this bibliometric study is to identify and analyze, in root canal disinfection, the 100 articles having the highest RCRs in the period 1990-2019, then compare them with the top 100 articles most cited. A cross-sectional study was performed, and the search strategy ((Disinfection AND root canal) AND (("1990/01/01"[Date-Publication]: "2019/12/31"[Date-Publication]))) relied on PubMed (n = 4294 documents), and article data were downloaded from the iCite database. The 100 articles with the highest RCRs and the top 100 cited were selected and evaluated in bibliometric terms. Among the 100 articles with the highest RCRs, there were no differences in the three decades for RCRs values, but there were in citations, being 2000-2009 the most cited. The USA was the predominant country (n = 30), followed by Brazil (n = 14). The most frequent study designs were reviews (n = 27) and in vitro (n = 25) and ex vivo (n = 24) studies. All subfields were well represented, although they varied over time. In 2010-2019, regenerative procedures and irrigation/disinfection techniques were predominant. Considering the RCR's top 100 articles, 76 were common with the 100 most cited articles. Using the RCR metric allowed us to identify influential articles in root canal disinfection, a research field with topics of significance that fluctuate over time. Compared to citations, RCR reduces the time from publication to detection of its importance for the readership and could be a valid alternative to citation counts.